Child care centres and preschool education - Ling, O.G. (1983)
Child care centres in Malaysia that were surveyed in 1982 offer in varying degrees of comprehensiveness, conventional programmes of activities for children below 4. Such activities define essentially the local conception of 'preschooling' for children in this age group. It is argued in this paper that such definition of preschool education are based on scanty knowledge of child development as applicable to the local conditions and Malaysian infants. To some extent, established kindergarten curricula and parental expectations have shaped the activities planned for the very young who are sent to child care centres. Hence, variety rather than consistency characterise the type of Programmes provided by child care centres. There are three identifiable forms of child care agencies viz. institute, home and estate based. Institute-based centres are generally professionally organised bases sponsored by private or state and voluntary supports and are often large to middle sized projects. Home-based operators are largely small-scale and servioes are provided in the minders' residences. Estates have for a long time organised their nurseries and kindergartens for children of the labourers and large numbers are involved at these child care centres. Gross disparities characterise the various types of centres even in considering a few aspects such as, the available: activities and facilities to Support these. The problem engendered in the inequalities assume social overtones especially with the concentration of Indians in the estates which generally pay very little note to activities and child care programmes. Other ethnic groups predominated at the institutes which generally subscribed most strongly to schedules of activities and the home-based centres.